Is the Long‐term Impact of a Multidomain Lifestyle Intervention on Cognitive Function Mediated by Changes in Leptin and Vascular Endothelial Growth Factor Concentrations?. (20th December 2022) - Espeland, Mark A.; Carmichael, Owen T.; Evans, Joni K; Hayden, Kathleen M.; Johnson, Karen C; Kahn, Steven; Luchsinger, Jose; Marvocina, Santica; Neiberg, Rebecca H.
Abstract: Background: The 10‐year intensive lifestyle intervention (ILI) of the Look AHEAD study resulted in a legacy of relative deficits in cognitive function among participants who entered the clinical trial with a history of cardiovascular disease or current obesity, as compared to participants assigned to the diabetes support and education (DSE) intervention. We hypothesized that levels of two weight‐sensitive proangiogenic cytokines, leptin and vascular endothelial growth factor (VEGF), which have been previously reported to be associated with cognitive function, may have been altered by the ILI and account for this concerning finding. Method: Concentrations of leptin and VEGF were determined using stored serum collected from 1, 279 participants at Look AHEAD baseline, proximal to cessation of the intervention (Epoch 1), and an average of 4 years later (Epoch 2). Masked clinic staff conducted up to four standardized assessments of cognitive function at times ranging from 8 to 18 years after baseline. A composite score was derived from tests of attention, executive function, and memory. Mixed effects models were used to assess relative differences in leptin and VEGF concentrations between intervention groups and whether these accounted for changes in cognitive composite scores, overall and within subgroups defined by baseline history of cardiovascular disease or obesity. Result: In both intervention groups, leptin concentrations increased from baseline to Epoch 1, and further between Epochs 1 and 2 (p<0.001). VEGF concentrations decreased between enrollment and Epoch 2 in both groups, and decreased substantially more between Epoch 1 and 2 in ILI than in DSE (p = 0.04). Overall, there was little evidence that leptin and VEGF concentrations were related to cognitive functioning. ILI‐DSE differences in VEGF, but not leptin, concentrations varied depending on baseline history of cardiovascular disease and obesity, but neither leptin or VEGF concentrations accounted for the relative decrements in cognitive function evident during long‐term follow‐up in participants assigned to ILI. Conclusion: Among persons with type 2 diabetes and either a history of cardiovascular disease or obesity, long‐term relative deficits in cognitive function associated with intensive lifestyle intervention are not related to differences in two weight‐sensitive proangiogenic cytokines.